Arabic Learning Material of Higher Education Muslim Community North Sulawesi - Wekke, Ismail Suardi (Dinamika Ilmu, 2017)
Arabic has a special characters and positions compare to bahasa Indonesia as the mother tongue of students. These conditions are prospect to create joyful learning and teaching. Therefore, through the teaching and learning it is the opportunity to accelerate the process of understanding source language. This research was conducted in higher education of north Sulawesi in Manado. Non-participant observation and in-depth interview were conducted to collect data. Four months of research was studied from May to September of 2016. There was three circles of focus group discussion in validating data for triangulation. This article shows that the learning material consists of two categories language competency and religious teaching. This study illustrate that learning material was integrated to teaching of Islam. Religious material used to developed interactive substantial discussion and the medium of conversation is the Arabic. Additional activities and class hour was programed to enhance student chance to learn and practice outside formal classroom. There were some instructors were provided to maintain student training for couple weeks. This research discusses that in the field of Arabic language learning emphasize constructing learning opportunity environments, it is important which contents are included and it is also studentsâ great interest how these contents are presented. Lecturers and instructors tried to provide instructional explanations. Furthermore, they communicate and demonstrate prior knowledge and student motivation in determining learning outcomes. The learning provides student opportunity to acquire conceptual knowledge and language competency. The article concludes by considering how embodied language material learning to religious content is the way to speed up two subject in one teaching for curriculum enhancement.